Development and Evaluation of a Thai Traditional Massage Shop Management System for Baan Saen Sabai - เติมผล, สันติ; ฤทธิ์ไธสง, ประไพศรี; อัศวจุฬามณี, ธัญญารัตน์; ศิริสุขเจริญพร, พรพงศ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
At present, many small Thai traditional massage shops still rely on traditional management methods. For example, service bookings are handled via phone calls or recorded in notebooks, which often leads to errors, data loss, duplicate bookings, and difficulty in quickly retrieving past information. This research aims to: (1) develop a management system for a Thai traditional massage shop, specifically for Baan Saensabai, and (2) evaluate the efficiency of the developed system. The system was designed and developed as a web application based on the System Development Life Cycle (SDLC). The system efficiency was evaluated by three experts in information system development, while user satisfaction was assessed by 25 users selected through purposive sampling. Data were collected using a 5-point Likert scale questionnaire, and the statistics used for data analysis included mean and standard deviation.           The results showed that the system efficiency, as evaluated by experts, was at a high level (mean = 4.41, SD = 0.56), and user satisfaction was also at a high level (mean = 4.43, SD = 0.57). These findings indicate that the system operates effectively, meets the intended objectives, and enhances the management efficiency of Baan Saen Sabai massage shop. Furthermore, the system can be applied to small businesses in the context of Thai traditional massage shops and can be further extended or adapted for use similar service-based businesses.